Intralobar Pulmonary Sequestration Presenting as Hemothorax Secondary to Spontaneous Pneumothorax: Case Report and Literature Review - Chen, Tian; Yu, Jie; Zhang, Na; Chen, Chenghao; Fu, Libing; Zeng, Qi (Frontiers in Pediatrics, 2022)
Introduction: Patients with pulmonary sequestration, a rare congenital lung malformation, are mostly asymptomatic. Recurrent localized infection is a major complication, while sudden hemothorax is extremely rare. We present a case of intralobar pulmonary sequestration presenting as hemothorax secondary to spontaneous pneumothorax, and comprehensively review the relevant literature. Case report: A 16-year-old male presented with chest pain after strenuous exercise. Chest X-ray showed a moderate pneumothorax. After admission and conservative treatment, he developed dizziness, amaurosis, and urinary incontinence. Bedside chest X-ray suggested a massive pleural effusion, and hemothorax was further identified via catheter drainage. Contrast-enhanced computed tomography was performed, and no abnormal blood vessels or leakage of contrast agent were observed. As the hemoglobin level continued to drop, exploratory thoracoscopic surgery was performed immediately. The abnormal systemic artery supplying the lung tissue was found to be ruptured; therefore, ligation of the abnormal artery with resection of the diseased lung tissue were performed. Pathological examination revealed nonspecific manifestations of pulmonary sequestration. He was followed up for 1 year without related complications. Conclusions: Our case suggests that the abnormal supply vessels of pulmonary sequestration are unstable, which may cause sudden hemothorax. Therefore, patients with pulmonary sequestration should undergo surgery promptly after diagnosis. In patients with hemothorax, we should consider the diagnosis of pulmonary sequestration; however, contrast-enhanced computed tomography or angiography cannot confirm the diagnosis in all cases. Surgical intervention is recommended in emergency settings.